2002
DOI: 10.1159/000065420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Human Sleep EEG Using Correlation Dimension Analysis

Abstract: Our study was designed to investigate the influence of alcohol on sleep using the correlation dimension (D2) analysis. Polysomnography (PSG) was performed in 10 adult human males during a baseline night (BL-N) and an ethanol (0.8 g/kg body weight) night (Et-N). The mean D2 values during the Et-N and BL-N decreased significantly from wakefulness to stages 1, 2, and 3+4 of nonrapid eye movement (non-REM) sleep, and increased during REM sleep. The mean D2 of the sleep electroencephalogram (EEG) during stage 2 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Chaos analysis can quantify certain characteristics of the EEG that are not readily visible to a naked-eye examination. Towards this end, studies have been performed on EEGs obtained from both (a) normal states of the brain such as sleep 65 73 and meditation, 74,75 as well as (b) pathological states such as schizophrenia 76 80 and epilepsy. 57,81 89…”
Section: Chaos Analysismentioning
confidence: 99%
“…Chaos analysis can quantify certain characteristics of the EEG that are not readily visible to a naked-eye examination. Towards this end, studies have been performed on EEGs obtained from both (a) normal states of the brain such as sleep 65 73 and meditation, 74,75 as well as (b) pathological states such as schizophrenia 76 80 and epilepsy. 57,81 89…”
Section: Chaos Analysismentioning
confidence: 99%
“…Ethanol caused a significant shortening of sleep latency in sleep-disturbed rats. On the other hand, it is reported that ethanol had no remarkable effect on sleep latency in healthy humans 7,8) ; however, there is no report whether ethanol showed a sleep-inducing effect in insomnia patients. Our present data in rats suggested that ethanol has the possibility of improving the insomniac's sleep.…”
Section: Discussionmentioning
confidence: 93%
“…4,6) On the other hand, there are many reports about the effect of ethanol on sleep latency and sleep pattern in healthy subjects or normal animals. [6][7][8] In connection with this, it is well known that many people who drink alcohol to help to fall asleep are not healthy but have trouble on sleeping. Therefore, there is a strong presumption that the effect of ethanol on insomniac patients is different from that in normal individuals.…”
mentioning
confidence: 99%
“…Desta forma, em modelos farmacológicos de sono, o composto que interfere nesses dois parâmetros de forma signifi cativa, possui efeito hipnótico. Com relação a esse efeito, o conjunto de fl orais utilizado neste trabalho (White chestnut, Agrymony e Vervain), produziu de forma signifi cativa [(F = 10,30) Como os RFB utilizados na terapêutica são normalmente diluídos em substância alcoólica (Van Haselen, 1999), a qual possui efeitos hipnóticos (Kobayashi et al, 2002), um grupo controle, com brandy (teor alcoólico de 38% nos 0,45 mLs administrado aos animais), também foi avaliado. Interessantemente, verifi cou-se que não houve modifi cações nos parâmetros experimentais relacionados ao sono dos animais prétratados com brandy quando comparados com o controle, o qual recebeu apenas o veículo no qual os fl orais testados foram diluídos (água mineral).…”
Section: Resultsunclassified